Tiger & Bunny. 2 - Sakakibara, Mizuki; Katsura, Masakazu; Nishida, Masafumi (Viz Media, 2013)
"Kotetsu and Barnaby are the first NEXT superhero duo, but they've got a few differences to overcome if they're going to learn to work together. A reality TV show intruding into their daily lives doesn't help, but a bomb threat just might get them to cooperate. Then a misguided surprise party leads to a NEXT-involved diamond heist!"